2021
DOI: 10.1021/acs.langmuir.0c03208
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Insights into Nanobubble Merging Studied Using In Situ Liquid-Phase Electron Microscopy

Abstract: Nanobubbles have attracted great interest in recent times due to their application in water treatment, surface cleaning and targeted drug delivery, yet the challenge remains to gain thorough understanding of their unique behavior and dynamics for their utilization in numerous potential 2 applications. In this work, we have used liquid phase electron microscopy technique to gain insights into the quasistatic merging of surface nanobubbles. The electron beam environment was controlled in order to suppress any ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Eqn (4) suggests that surface nanobubbles with a large footprint radius in open systems like those observed by AFM or optical methods cannot have an ultrahigh density of tens to hundreds kg m −3 except for inside the adsorbed layers. In contrast, because the typical footprint radius of nanobubbles observed by LPEM is at most tens of nanometers, 54–56 the bulk density inside them can reach a hundred kg m −3 . In addition, when a contact angle is 90°, the gas density estimated using eqn (4) corresponds to that inside the bulk nanobubbles in which the footprint radius R FP is defined as the radius of curvature.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Eqn (4) suggests that surface nanobubbles with a large footprint radius in open systems like those observed by AFM or optical methods cannot have an ultrahigh density of tens to hundreds kg m −3 except for inside the adsorbed layers. In contrast, because the typical footprint radius of nanobubbles observed by LPEM is at most tens of nanometers, 54–56 the bulk density inside them can reach a hundred kg m −3 . In addition, when a contact angle is 90°, the gas density estimated using eqn (4) corresponds to that inside the bulk nanobubbles in which the footprint radius R FP is defined as the radius of curvature.…”
Section: Resultsmentioning
confidence: 90%
“…One is the overestimation of the gas density inside the nanobubbles in STXM observations caused by the existence of an ultradense gas molecule-adsorbed layer underneath them. The formation of the dense adsorbed layers of gas molecules has been reported not only by MD simulations 22,24,40 but also by AFM 40,50–52 and LPEM 53,54 experiments. Our analysis also found that even when the pressure P gas was reduced to 0.2 MPa corresponding to the nanobubbles with a footprint radius of 250 nm and a contact angle of 170°, the peak density inside the adsorbed layer was 37 and 241 kg m −3 for η = 1.0 and 1.5 (shown in ESI Fig.…”
Section: Resultsmentioning
confidence: 94%
“…As illustrated in previous reports of in situ TEM experiments of nanoscale contact angles and nanobubbles, , a graphene liquid cell is assembled by two graphene membranes on TEM grids where distilled water is sandwiched in between, Figure a. The liquid cell is then mounted on a TEM sample holder with a temperature control mechanism and is imaged in a Hitachi H7600 TEM system at a 100 kV electron beam voltage.…”
Section: Methods and Materialsmentioning
confidence: 99%